2015
DOI: 10.1371/journal.pone.0128561
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Metabolic Pathways Affected in the Mouse Model of Barth Syndrome

Abstract: Cardiolipin (CL) is a mitochondrial phospholipid essential for electron transport chain (ETC) integrity. CL-deficiency in humans is caused by mutations in the tafazzin (Taz) gene and results in a multisystem pediatric disorder, Barth syndrome (BTHS). It has been reported that tafazzin deficiency destabilizes mitochondrial respiratory chain complexes and affects supercomplex assembly. The aim of this study was to investigate the impact of Taz-knockdown on the mitochondrial proteomic landscape and metabolic proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 58 publications
11
61
0
Order By: Relevance
“…BTHS mitochondria have reduced levels of super complexes and display decreased stability of existing super complexes [30,37]. In keeping with this, Huang et al [38] reported that ETC super complexes are destabilized in cardiolipin-depleted mitochondria from taz knockdown mouse hearts, an effect that potentially has an adverse affect on metabolic channeling of reducing equivalents. Likewise, Kiebish et al [39] reported that loss of tafazzin function in myocardium leads to changes in the mitochondrial lipidome, resulting in the dysregulated generation of oxidized derivatives of polyunsaturated fatty acids.…”
Section: Altered Cardiolipin Composition Affects the Electron Transpomentioning
confidence: 83%
“…BTHS mitochondria have reduced levels of super complexes and display decreased stability of existing super complexes [30,37]. In keeping with this, Huang et al [38] reported that ETC super complexes are destabilized in cardiolipin-depleted mitochondria from taz knockdown mouse hearts, an effect that potentially has an adverse affect on metabolic channeling of reducing equivalents. Likewise, Kiebish et al [39] reported that loss of tafazzin function in myocardium leads to changes in the mitochondrial lipidome, resulting in the dysregulated generation of oxidized derivatives of polyunsaturated fatty acids.…”
Section: Altered Cardiolipin Composition Affects the Electron Transpomentioning
confidence: 83%
“…It has been established that CL deficiency can be responsible for the instability of cristae membrane supercomplexes [85]. Indeed, the abundance of such supercomplexes was found to be low in BTHS [45, 86, 87]. However, new data from our laboratory suggest that supercomplex instability may be the cause rather than the effect of CL deficiency in BTHS.…”
Section: Abnormal CL Metabolism In Barth Syndromementioning
confidence: 84%
“…Changes in cardiac proteome have been identified and measured in TAZ knockdown mouse models of human Barth syndrome. 175 The ability to generate induced pluripotent stem cell-cardiomyocyte models from individuals with Barth syndrome is an important development that may speed the assessment of potential therapies to correct the metabolic phenotype of the disease. 176 …”
Section: Noncompaction Cardiomyopathymentioning
confidence: 99%